2009
DOI: 10.1530/eje-09-0333
|View full text |Cite
|
Sign up to set email alerts
|

Which patients with acromegaly are treated with pegvisomant? An overview of methodology and baseline data in ACROSTUDY

Abstract: Context: Pegvisomant (Somavert, Pfizer Inc.) is the first and only available GH receptor antagonist. ACROSTUDY is an international surveillance study that offers inclusion in a web-based registry to all patients with acromegaly treated with pegvisomant; it aims at monitoring long-term safety and efficacy of this compound. Results: Of all patients, 80% were reported to have had surgery and 33% to have received radiation therapy. Of the 792 patients, 14% had received no prior medical treatment before pegvisomant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 23 publications
4
20
0
1
Order By: Relevance
“…And in a study by Parkinson et al [21] in 118 acromegalic patients, gender, body weight, previous radiotherapy, and baseline GH/IGF-1 influenced the pegvisomant dosage that was needed to reach biochemical control. Additionally, the role of the diabetes status in the pegvisomant therapy scheme has been emphasized as patients with acromegaly and type 2 diabetes mellitus require higher pegvisomant dosages to achieve IGF-1 normalisation than acromegalic patients without diabetes mellitus [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…And in a study by Parkinson et al [21] in 118 acromegalic patients, gender, body weight, previous radiotherapy, and baseline GH/IGF-1 influenced the pegvisomant dosage that was needed to reach biochemical control. Additionally, the role of the diabetes status in the pegvisomant therapy scheme has been emphasized as patients with acromegaly and type 2 diabetes mellitus require higher pegvisomant dosages to achieve IGF-1 normalisation than acromegalic patients without diabetes mellitus [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, different efficacies of PEG-V are reported ranging from around 60 to over 90% [10,11,12,13,14,15]. The studies that reported lower efficacy levels are all observational studies [11,12,14,15,16].…”
Section: Efficacy In Controlling Gh and Igf-imentioning
confidence: 99%
“…The studies that reported lower efficacy levels are all observational studies [11,12,14,15,16]. These observational studies were not designed to assess efficacy but were designed to assess additional medical information, such as rare side effects and other safety aspects.…”
Section: Efficacy In Controlling Gh and Igf-imentioning
confidence: 99%
“…Several interim analysis from ACROSTUDY have been published. [25][26][27][28] The last publication 26 included 1,288 patients. After 5 years of PEG treatment, 63.2% of cases had normal IGF-I levels.…”
Section: Efficacy Of Peg In Clinical Studiesmentioning
confidence: 99%
“…2 Combination therapy, usually with daily PEG, 26 is increasingly being used in recent years. While in the GPOS no cases of combined treatment were described, 30 in the ACROSTUDY 2009, 27 22.4% of the patients were receiving combination therapy with PEG plus SSA and 3.8% PEG plus SSA plus CAB. In ACROSTUDY 2012, 26 36.6% of subjects were on combination therapy.…”
Section: Peg Plus Long Acting Ssamentioning
confidence: 99%